A META-ANALYSIS ON COMPLETE AND PARTIAL MOLAR PREGNANCY. - Rahman, Emrana (Student's Journal of Health Research Africa, 2023)
Background: The hydatidiform mole is an uncommon gynecological condition that arises from trophoblastic cells. Post-molar pregnancies can result in multiple abortions, stillbirths, preterm deliveries, or live births, or they can recur in subsequent molar pregnancies. The literature on the obstetric outcomes of molar pregnancies is limited, frequently consisting of monocentric studies and national database data. This review and meta-analysis aimed to examine the obstetric outcomes of complete (CHM) and partial (PHM) molar pregnancies managed conservatively. Following MOOSE and PRISMA, a meta-analysis was conducted. Methods: Six studies met the inclusion criteria. Included were 13,129 complete (52,1%) and 12,093 incomplete (47.9%) molar pregnancies out of a total of 25,222 patients. Results: The rate of live births after CHM was significantly higher (p = 0.002) than after PHM (53.6% vs. 51.0%, 3266 vs. 1807 cases, respectively). I2 = 57.7%, the pooled proportion = 0.2%, and the 95% Confidence Interval (CI) ranged from 0.6 to 0.9. There was no statistically significant difference between CHM and PHM with regard to ectopic pregnancies (p = 0.633), miscarriage (p = 0.637), preterm birth (p = 0.865), stillbirth (p = 0.911), termination of pregnancy (p = 0.572), or complete molar recurrence (p = 0.580). Partial molar recurrence was more common following PHM than CHM (0.4% vs. 0.3%, 52 vs. 37 cases, p = 0.002). Conclusion: Patients desiring additional pregnancies should receive careful counseling on the outcomes of subsequent obstetric pregnancies, and further research is required to confirm these results.